The relationship between of international migration, income per capita and unemployment rate in Indonesia - Siti Komariyah; R. Alamsyah Sutantio (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
International migration has become an interesting issue in recent decades as globalization has become increasingly widespread as a form of openness in the world economy. This economic openness also results in changes in life socially, economically and culturally more dynamically. One of the dynamics of socio-economic conditions is shown by the increasingly flexible and dynamic international migration that occurs in several countries. Some underlying factors include conditions of income and unemployment. This study aims to analyse the response of migration when there is dynamics in per capita income as a proxy for welfare and unemployment as a proxy for employment conditions. VAR analysis is a method to see these responses through the IRF. The results of the analysis showed a significant response from migration as a result of the shock that occurred in both variables and with OLS estimation, both of these variables have a significant impact on influencing Indonesia's international migration flow. These is a signal that the main factor causing international migration is dominant due to the dynamics of income and labour market conditions (unemployment) in Indonesia. Although in other cases, migration also has a positive impact on some parties such as increasing income per capita for migrants, reducing unemployment and increasing the country's foreign exchange, but this condition also needs proper supervision and management. This must also be considered from various other aspects such as demographic conditions related to the age structure of the population and availability of employment to create a balance in the labour market